2020
DOI: 10.3389/fcell.2020.00200
|View full text |Cite
|
Sign up to set email alerts
|

Mitophagy: An Emerging Role in Aging and Age-Associated Diseases

Abstract: Mitochondrial dysfunction constitutes one of the hallmarks of aging and is characterized by irregular mitochondrial morphology, insufficient ATP production, accumulation of mitochondrial DNA (mtDNA) mutations, increased production of mitochondrial reactive oxygen species (ROS) and the consequent oxidative damage to nucleic acids, proteins and lipids. Mitophagy, a mitochondrial quality control mechanism enabling the degradation of damaged and superfluous mitochondria, prevents such detrimental effects and reins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
159
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 247 publications
(192 citation statements)
references
References 223 publications
0
159
2
Order By: Relevance
“…In this context, two major processes are for protection from harmful effects of ROS, including mitophagy and antioxidant capacity. In one hand, mitophagy, which is characterized by autophagic degradation of mitochondria, decreased with aging [56]. On the other hand, decreased mitophagy, together with decreased antioxidant capacity during aging can increased ROS levels in the body.…”
Section: Aging and Autophagymentioning
confidence: 99%
“…In this context, two major processes are for protection from harmful effects of ROS, including mitophagy and antioxidant capacity. In one hand, mitophagy, which is characterized by autophagic degradation of mitochondria, decreased with aging [56]. On the other hand, decreased mitophagy, together with decreased antioxidant capacity during aging can increased ROS levels in the body.…”
Section: Aging and Autophagymentioning
confidence: 99%
“…In addition to Parkin, several other E3 ligases have been shown to be involved in mitophagy, e.g., MUL1, ARIH1, and MARCH5 (225)(226)(227). Several mitophagy-specific receptors, such as FUDNC1, NIX, BNIP3, PHB2, and BCL2L13, have been reported to recognize damaged mitochondria, interact with LC3 and recruit autophagosomes decorated by LC3 (228)(229)(230). NLRX1 has recently been identified as a new mitophagy receptor in L. monocytogenes (231).…”
Section: Mitochondrial Dynamics and Mitophagymentioning
confidence: 99%
“…Network pharmacology reveals the complex antiaging mechanism of resveratrol through multitarget, multi-pathway and multi-pathway, and discusses the potential antiaging target of resveratrol, which provides clues and reference directions for the follow-up animal experiments, and lays a good foundation for further discussion of the antiaging pharmacological target and molecular mechanism of resveratrol. Aging is closely related to oxidative stress, endoplasmic reticulum stress and apoptosis (Chen G. et al, 2020;Kandlur et al, 2020). SOD, GSH-Px, CAT, AE, MDA are considered to be related to oxidative stress, and they were found that SOD, GSH-Px, CAT, AE, MDA worked as important parameters reflecting the potential antiaging ability of the body by many previous reasearches (Akbulut et al, 2009;Hui et al, 2020;Song et al, 2020).…”
Section: Discussionmentioning
confidence: 99%